Course of screening-based depression in young adults with a long type 1 diabetes duration: Prevalence and transition probabilities – A cohort study. (March 2022) - Baechle, Christina; Stahl-Pehe, Anna; Castillo, Katty; Lange, Karin; Holl, Reinhard W.; Rosenbauer, Joachim
Highlights: The prevalence of screening-based depression (SBD) was 17.7% in women/7.0% in men. The prevalence of SBD varied with age, sex, HbA1c, and smoking behavior. Transition probabilities for developing SBD were more than twofold higher in women. Previous SBD, living arrangement and German region mainly predicted current SBD. Results emphasize the relevance of regular depression screenings in young adults. Abstract: Aims: To extend the current knowledge of the prevalence and course of screening-based depression (SBD) and its predictors in emerging adults with a long type 1 diabetes duration. Methods: A total of 487 young adults (64.7% women, mean age 24.0 years) who participated in a nationwide cohort study provided data on SBD (Patient Health Questionnaire (PHQ-9) score ≥ 10). We estimated the overall and age- and sex-specific prevalence of SBD, identified the associated covariates, and determined the transition probabilities between SBD states using adjusted first-order Markov transition models. Results: The prevalence of SBD was 17.7% in women and 7.0% in men. A total of 70.4% (95%-CI 57.4%; 80.8%) of the participants with SBD at the first screening still had SBD at the three-year follow-up. Of the subjects without SBD at baseline, 6.9% (4.9%; 9.8%) had SBD at follow-up. The main predictor of current SBD was previous SBD (OR 39.0 (15.4; 98.6)), followed by living in one's own or in a shared apartment vs. living with both parents (OR: 2.75 (1.03; 7.36)). Conclusions: Using an innovative analytical approach, emerging adults with a long diabetes duration demonstrated a moderate rate of incident SBD but a high rate of persistent SBD.